Fortyfikacje Prus Wschodnich w XVIII wieku - Podruczny, Grzegorz (Muzeum Historyczne w Ełku, 2015)
The article concerns 18th century fortifications in East Prussia. Through the prism of changes in defense architecture, it shows changes in the meaning of provincial areas in the Brandenburg-Prussian state. Architectural plans of fortresses and correspondence from the era constitute the basic source material. The article discusses the fortresses of Piława, Klaipeda, Konigsberg and Lyck. The failed attempt at building a fortress in Grabow is also analyzed, its cause is seen in the unsuitable choice of location. The unrealized plans for the building of the Szczytno Fortress are also noted.
Fortifications of East Prussia in the 18th century
Keywords: Prusy Wschodnie, historia fortyfikacji, architektura obronna, twierdza, Piława, Fort Lyck, Szczytno; East Prussia, history of fortification, defence architecture, fortress, Pillau, Fort Lyck, Ortelsburg